Correcting ionospheric effects and monitoring two-dimensional displacement fields with multiple-aperture InSAR technology with application to the Yushu earthquake - Jun Hu; ZhiWei Li; Lei Zhang; XiaoLi Ding; JianJun Zhu; Qian Sun; Wei Ding (Science China Earth Sciences, 2012)

Overexpression of actin-depolymerizing factor blocks oxidized low-density lipoprotein-induced mouse brain microvascular endothelial cell barrier dysfunction - Jun Wang; Lu Sun; Yan-Fang Si; Bao-Min Li (Molecular and Cellular Biochemistry, 2012)

Performance of four Chinese Trichogramma species as biocontrol agents of the rice striped stem borer, Chilo suppressalis, under various temperature and humidity regimes - Xiao-Hua Yuan; Li-Wei Song; Jun-Jie Zhang; Lian-Sheng Zang; Li Zhu; Chang-Chun Ruan; Guang-Zhi Sun (Journal of Pest Science, 2012)

T-2 Toxin Contamination in Grains and Selenium Concentration in Drinking Water and Grains in Kaschin–Beck Disease Endemic Areas of Qinghai Province - Li-Yan Sun; Qiang Li; Fan-Gang Meng; Ying Fu; Zhi-Jun Zhao; Li-Hua Wang (Biological Trace Element Research, 2012)

Evaluation of a DNA vaccine candidate co-expressing GP3 and GP5 of porcine reproductive and respiratory syndrome virus (PRRSV) with interferon α/γ in immediate and long-lasting protection against HP-PRRSV challenge - Yijun Du; Jing Qi; Yu Lu; Jiaqiang Wu; Dongwan Yoo; Xing Liu; Xiumei Zhang; Jun Li; Wenbo Sun; Xiaoyan Cong; Jianli Shi; Jinbao Wang (Virus Genes, 2012)

Comparative analysis of water stress-responsive transcriptomes in drought-susceptible and -tolerant wheat (Triticum aestivum L.) - Yong Chun Li; Fan Rong Meng; Chun Yan Zhang; Ning Zhang; Ming Shan Sun; Jiang Ping Ren; Hong Bin Niu; Xiang Wang; Jun Yin (Journal of Plant Biology, 2012)

Satellite monitoring of massive green macroalgae bloom (GMB): imaging ability comparison of multi-source data and drifting velocity estimation - Ting-Wei Cui; Jie Zhang; Li-E Sun; Yong-Jun Jia; Wenjing Zhao; Zong-Ling Wang; Jun-Min Meng (International Journal of Remote Sensing, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Nocardioides panzhihuaensis sp. nov., a novel endophytic actinomycete isolated from medicinal plant Jatropha curcas L. - Sheng Qin; Bo Yuan; Yue-Ji Zhang; Guang-Kai Bian; Tomohiko Tamura; Bing-Zhi Sun; Wen-Jun Li; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2012)

Relationship of summer soil moisture with early winter monsoon and air temperature over eastern China - Ge Liu; Jun‐Ming Chen; Li‐Ren Ji; Shu‐Qing Sun (International Journal of Climatology, 2012)
The time‐lagged effect of summer soil moisture (SM) on ensuing winter climate in eastern China is examined. The East Asian winter monsoon (EAWM) in early winter (November) and associated air temperature over eastern China are shown to significantly correlate with the previous summer (June–August) SM in eastern China with a center located at the lower reaches of the Yellow River (LRYR). The positive anomalies of summer SM, persisting for a few months, may act as a buffer to defer the ground cooling of eastern China in early winter mainly through modulating thermal capacity. And the warmer ground of eastern China could lead to a warmer air temperature above the ground through direct land–air interactions and through indirectly adjusting the EAWM which is sensitive to the land–sea thermal contrast. These results provide an empirical predictor for the EAWM and for the variability of air temperature over eastern China in early winter. Copyright © 2011 Royal Meteorological Society

Structural insights into a human anti-IFN antibody exerting therapeutic potential for systemic lupus erythematosus - Songying Ouyang; Bin Gong; Jin-Zhi Li; Li-Xia Zhao; Wei Wu; Fu-Shun Zhang; Lina Sun; Shu-Jun Wang; Meng Pan; Chuan Li; Wenguang Liang; Neil Shaw; et al. (Journal of Molecular Medicine, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

Expressions of GRP78 and Bax associate with differentiation, metastasis, and apoptosis in non-small cell lung cancer - Qing Sun; Jun Hua; Qi Wang; Wei Xu; Jiaxing Zhang; Jun Zhang; Jiuhong Kang; Maoquan Li (Molecular Biology Reports, 2012)

Preliminary investigation of quantified detection of airborne T-2 and HT-2 toxins in one henhouse - Xiaodong Sun; Jun Li; Yaling Wang; Guozhong Lu; Lijun Sun; Yi Ouyang (Aerobiologia, 2012)

De novo characterization of the root transcriptome of a traditional Chinese medicinal plant Polygonum cuspidatum - DaCheng Hao; Pei Ma; Jun Mu; ShiLin Chen; PeiGen Xiao; Yong Peng; Li Huo; LiJia Xu; Chao Sun (Science China Life Sciences, 2012)

Fetal exposure to bisphenol A affects the primordial follicle formation by inhibiting the meiotic progression of oocytes - Han-Qiong Zhang; Xi-Feng Zhang; Lian-Jun Zhang; Hu-He Chao; Bo Pan; Yan-Min Feng; Lan Li; Xiao-Feng Sun; Wei Shen (Molecular Biology Reports, 2012)

Association between CYP1A1 polymorphism and colorectal cancer risk: a meta-analysis - Yuan Zheng; Jing-Jun Wang; Liang Sun; Hong-Lei Li (Molecular Biology Reports, 2012)

Fertilization increases paddy soil organic carbon density - Shao-xian Wang; Xin-qiang Liang; Qi-xiang Luo; Fang Fan; Ying-xu Chen; Zu-zhang Li; Huo-xi Sun; Tian-fang Dai; Jun-nan Wan; Xiao-jun Li (Journal of Zhejiang University-SCIENCE B, 2012)

Co-expression and Synergism Analysis of Vip3Aa29 and Cyt2Aa3 Insecticidal Proteins from Bacillus thuringiensis - Xiumei Yu; Tao Liu; Zhiguang Sun; Peng Guan; Jun Zhu; Shiquan Wang; Shuangcheng Li; Qiming Deng; Lingxia Wang; Aiping Zheng; Ping Li (Current Microbiology, 2012)

Role of calcineurin in the VTA in rats behaviorally sensitized to methamphetamine - Jun Wang; Li-Li Sun; Wei-Li Zhu; Yan Sun; Jian-Feng Liu; Lin Lu; Jie Shi (Psychopharmacology, 2012)

p38 MAPK regulates calcium signal-mediated lipid accumulation through changing VDR expression in primary preadipocytes of mice - Chao Sun; Renli Qi; Li Wang; Jun Yan; Yong Wang (Molecular Biology Reports, 2012)

Virus-binding activity of the truncated C subunit of porcine aminopeptidase N expressed in Escherichia coli - Dongbo Sun; Hongyan Shi; Jianfei Chen; Donghua Guo; Quan Liu; Xianjing He; Jun Bao; Yunfeng Wang; Huaji Qiu; Li Feng (Biotechnology Letters, 2012)

Phylogenetic assessment and biogeographic analyses of tribe Peracarpeae (Campanulaceae) - Zhuo Zhou; Jun Wen; Guodong Li; Hang Sun (Plant Systematics and Evolution, 2012)

Calcium ameliorates obesity induced by high-fat diet and its potential correlation with p38 MAPK pathway - Chao Sun; Li Wang; Jun Yan; Shumin Liu (Molecular Biology Reports, 2012)

The effect of sevoflurane on the expression of M1 acetylcholine receptor in the hippocampus and cognitive function of aged rats - Sheng Peng; Yan Zhang; Guo-Jun Li; Deng-Xin Zhang; Da-Peng Sun; Qiang Fang (Molecular and Cellular Biochemistry, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

Bisphenol A exposure modifies methylation of imprinted genes in mouse oocytes via the estrogen receptor signaling pathway - Hu-He Chao; Xi-Feng Zhang; Bo Chen; Bo Pan; Lian-Jun Zhang; Lan Li; Xiao-Feng Sun; Qing-Hua Shi; Wei Shen (Histochemistry and Cell Biology, 2012)

RNA interference and ischemic injury - Min Liu; Jin Sun; Wen Wang; Jia-Wang Ding; Shu-Guo Li; Shubash Adhikari; Li Li; Jun Yang (Molecular Biology Reports, 2012)

Unloading the infarcted heart affect MMPs–TIMPs axis in a rat cardiac heterotopic transplantation model - Wei-jian Wang; Zi-li Meng; Yun-chang Mo; Jun-wei Liu; Cheng-chao Sun; Sheng-shou Hu; Hao Zhang (Molecular Biology Reports, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.